CHANGES IN THE SMALL INTESTINE IN PULMONARY FIBROSIS. THE BODY'S RESPONSE TO EXPERIMENTAL PULMONARY FIBROSIS. THE RESULT OF THE EXPERIMENTS (Conferencea, 2022)
In this review, we discuss three broad areas which have been explored that may be responsible for the combination of altered lung fibroblasts, loss of alveolar epithelial cells, and excessive accumulation of ECM: inflammation and immune mechanisms, oxidative stress and oxidative signaling, and procoagulant mechanisms.